2000
DOI: 10.1038/sj.ijir.3900612
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results with Nesbit's procedure as treatment of Peyronie's disease

Abstract: The objective was to assess sexual function at long-term follow-up after the Nesbit operation for Peyronie's disease.One hundred and ®fty seven out of 213 patients treated between 1986 and 1998 using the Nesbit procedure were reassessed by means of IIEF-5 questionnaire together with two questions about residual deformity and treatment satisfaction. The results from this questionnaire together with the patient case records constitute the basis of this paper.After an average 72-month follow-up subjective patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 20 publications
4
32
0
4
Order By: Relevance
“…In four (17%) of these studies, the sole intervention was surgery and comprised Nesbit operation for Peyronie's disease, 29 venous stripping surgery, 30 prostaImpact of SHIM JC Cappelleri and RC Rosen 31 and surgery for penile fracture. 32 In seven (30%) of the 23 studies, the active interventions included sildenafil for patients with ED, 5,33 sildenafil plus patient education for patients with ED, [34][35][36] sildenafil for patients with ED and arterial hypertension, 37 and, in one study, sildenafil in young healthy men.…”
Section: Intervention Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In four (17%) of these studies, the sole intervention was surgery and comprised Nesbit operation for Peyronie's disease, 29 venous stripping surgery, 30 prostaImpact of SHIM JC Cappelleri and RC Rosen 31 and surgery for penile fracture. 32 In seven (30%) of the 23 studies, the active interventions included sildenafil for patients with ED, 5,33 sildenafil plus patient education for patients with ED, [34][35][36] sildenafil for patients with ED and arterial hypertension, 37 and, in one study, sildenafil in young healthy men.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…4,5 In one study, the 'normal' score used for no ED (26)(27)(28)(29)(30) suggested that the Erectile Function (EF) domain of the IIEF was used instead of the SHIM (or 'IIEF-5'). 38 In another study, a score of less than 21 (instead of less than or equal to 21) was used to classify ED.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Further, the disease itself and the associated psychological stress are obviously degrading the life quality of the patients [1][2][3]. The reported prevalence of PD varies from 0.4 to 9% of adult men, and most cases happened after their 40s.…”
Section: Introductionmentioning
confidence: 98%
“…Currently, while lengthening procedures are recommended to patients with severe or complex deformities, shortening procedures (Nesbit technique or plication procedure) are usually recommended to patients with simple curvatures \60° [ 2,12,13]. In order to present better medical service, urologists have been exerting novel modifications, and some recent data were really attractive with improved objective surgery results and subjective satisfaction [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…2 Clinically, PD presents as any combination of penile pain, penile curvature and ED, and depresses the patient and partner both physically and psychologically. 3 Many cases resolve with no treatment; but if left untreated PD can cause fibrotic, nonexpansible thickening of relatively distinct areas of the corpora tunica, known as plaque formation. Clinical manifestations of penile plaque are penile deformity, penile pain and varying degrees of ED.…”
Section: Introductionmentioning
confidence: 99%